2023
DOI: 10.3390/ijms24032205
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs in Cell-to-Cell Communication: Exploiting Physiological Mechanisms as Therapeutic Targets in Cardiovascular Pathologies

Abstract: Cardiovascular disease, the leading cause of death worldwide, has been characterized at the molecular level by alterations in gene expression that contribute to the etiology of the disease. Such alterations have been shown to play a critical role in the development of atherosclerosis, cardiac remodeling, and age-related heart failure. Although much is now known about the cellular and molecular mechanisms in this context, the role of epigenetics in the onset of cardiovascular disease remains unclear. Epigenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…Advanced studies have shown that therapeutic strategies based on specific ncRNA modulation are promising candidates to improve CVDs ( 28 , 125 , 126 ). NcRNAs are also considered to be key novel regulators of cardiovascular function and risk factors, potentially serving as small-molecule targets (e.g., miRNAs, lncRNAs, circRNAs and lincRNAs) or gene silencing tools (e.g., siRNAs) for cardiovascular treatment and prognosis assessment ( 23 , 28 ).…”
Section: Prognostic and Therapeutic Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…Advanced studies have shown that therapeutic strategies based on specific ncRNA modulation are promising candidates to improve CVDs ( 28 , 125 , 126 ). NcRNAs are also considered to be key novel regulators of cardiovascular function and risk factors, potentially serving as small-molecule targets (e.g., miRNAs, lncRNAs, circRNAs and lincRNAs) or gene silencing tools (e.g., siRNAs) for cardiovascular treatment and prognosis assessment ( 23 , 28 ).…”
Section: Prognostic and Therapeutic Targetsmentioning
confidence: 99%
“…First, RNA molecules may evoke the host’s immune system and result in adverse immune responses. Second, because of the general nature of their targets, ncRNA-based drugs might not target specific sites ( 125 ). Therefore, current studies have proposed that ncRNAs combined with biocompatible nanoparticles (NPs) can offer better therapeutic properties.…”
Section: Prognostic and Therapeutic Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…A plethora of studies demonstrated the importance of ncRNAs in the cardiovascular system and their involvement in cell-to-cell communication [ 8 , 22 ]. In fact, it is now well known that ncRNAs are considered important communication molecules due to their potential to modulate gene expression at intra- and extra-cellular levels, being secreted or transported to other cell types [ 19 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, exosomes, the smallest kind of extracellular vesicles, are able to carry different cargos, including RNAs, proteins, and lipids, which can have an impact on the target cell biology by regulating a plethora of different functions [ 23 , 28 ]. Exosomes are secreted by all cells under physiological and pathological conditions and are released by all cells from the cardiovascular system [ 29 ].…”
Section: Introductionmentioning
confidence: 99%